An alternative supporting electrolyte for enzyme immobilization in conducting polymers - KARATAŞ, SEVİM (ELSEVIER SCIENCE BV, 2008)
In this study an alternative supporting electrolyte was used in enzyme immobilization. Invertase was studied to observe the effect of the supporting electrolyte. Sulfonated poly(arylene ether sulfone) was used as the supporting electrolyte during the electrolysis of pyrrole. The results show that the polymeric supporting electrolyte can be used instead of sodium dodecyl sulfate. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: supporting electrolyte; enzyme immobilization; conducting polymers; POLYPHENOL OXIDASE; PHENOLIC-COMPOUNDS; MENTHYL ESTER; THIN-FILMS; RED WINES; COPOLYMERS; GLUCOSE; INVERTASE; PYRROLE; SENSOR